Numerical modeling of the thermal contact in metal forming processes - Martins, J. M. P. (2016)
Heat flow across the interface of solid bodies in contact is an important aspect in several engineering applications. This work presents a finite element model for the analysis of thermal contact, which takes into account the effect of contact pressure and gap dimension in the heat flow across the interface between two bodies. Additionally, the frictional heat generation is also addressed, which is dictated by the contact forces predicted by the mechanical problem. The frictional contact problem and thermal problem are formulated in the frame of the finite element method. A new law is proposed to define the interfacial heat transfer coefficient (IHTC) as a function of the contact pressure and gap distance, enabling a smooth transition between two contact status (gap and contact). The staggered scheme used as coupling strategy to solve the thermomechanical problem is briefly presented. Four numerical examples are presented to validate the finite element model and highlight the importance of the proposed law on the predicted temperature.